A descriptive study of the interior lighting conditions in selected households in a low-income community in Metro Manila - Valdez, Angelie N.
This study discusses the current lighting conditions of ten selected households in the Gawad Kalinga Laura community located along Commonwealth Avenue, Quezon City. The lighting condition, which includes both natural and artificial sources, was characterized by the lighting practices and the activities of the family. The study aimed to find out what the implications of such lighting conditions are to the family. These implications were based on three main objectives of light presented by the Philips Lighting (1993) namely: to provide (1) visual performance, (2) visual comfort and pleasantness and (3) cost and energy effectiveness. Ten (10) respondents were interviewed and their houses documented. Random sampling was used to determine the 10 households to be interviewed and photodocumented while convenience sampling was utilized for the 20 households included in the survey that supported the findings. The results of the interview revealed that the respondents are satisfied with their current lighting condition. However, upon computing the illuminance level, the researcher discovered that the current lighting is not conducive to most tasks. Among the three objectives of light, cost and energy effectiveness was present. The two other objective were not. Because visual discrimination exists, the families already adapted to their current lighting condition even if the illuminance level did not meet the standards given by the Illuminationg Engineering Society (IES). The researcher recommends the use of a more detailed illuminance calculation for future studies. For the community, it is recommended that the use of natural lighting be maximized as much as possible to minimize electricity consumption.